The effect of recombinant human interferon α1b treatment of infants hospitalized with lower respiratory tract infection on subsequent wheezing - Lihua Yang; Guocheng Zhang; Lusheng Huang; Xiaoling Ren; Yanqi Su; Chengxiu Wang; Yuanbin Shi; Liao Li; Hui Shan; Jing Chen; Jianxin Xiong; Xue Xue; et al. (Elsevier, 2021)
Objective: To investigate the impact of recombinant human interferon α1b (rhIFNα1b) treatment in infants hospitalized with lower respiratory tract infections on subsequent wheezing. Methods: The clinical data of infants (n = 540) with viral pneumonia, wheezy bronchitis, or bronchiolitis hospitalized in 19 Chinese hospitals from June 2009 to June 2015 were retrospectively analyzed. The parameters relevant to wheezing episodes within the last year were collected by telephone and questionnaires. The rhIFNα1b treatment group (n = 253) and control group (n = 287) were compared in terms of wheezing episodes within the last year. Moreover, the wheezing group (95 cases) and non-wheezing group (445 cases) were compared. Results: Out of 540 cases, 95 (17.6%) experienced wheezing episodes, 13.8% (35/253) cases treated with rhIFNα1b, and 20.9% (60/287) cases without rhIFNα1b experienced wheezing episodes within the last year. The rhIFNα1b treatment significantly improved wheezing episodes within the last year, compared with the control peers (p = 0.031). Single-factor regression showed statistically significant differences between the wheezing and non-wheezing groups in terms of age, rhIFNα1b use, childhood and family history of allergy, housing situation, and feeding history (p < 0.05). Binary logistic regression showed a childhood history of allergy (OR = 2.14, p = 0.004), no rhIFNα1b use (OR = 1.70, p = 0.028), and living in a crowded house (OR = 1.92, p = 0.012) might be risk factors of subsequent wheezing. Accordingly, breastfeeding (OR = 0.44, p = 0.008) and hospitalization age of ≤1-year-old (OR = 0.58, p = 0.024) were protective factors. Conclusions: Early use of rhIFNα1b in infants hospitalized with lower respiratory tract infections and breastfeeding could prevent subsequent wheezing. Living in a crowded house could promote subsequent wheezing.